PSEUDOANEURYSM OF BRACHIAL ARTERY: CASE REPORT OF A RARE CASE - Nayab Alia; Shama Aslam; Nosheen Ahmad (Journal of University Medical & Dental College, 2015)
ABSTRACT: Brachial artery Pseudo-aneurysm is a rare entity, only very few cases are reported in literature at present while most of them are due to a known cause. A patient was referred to our department of Diagnostic Radiology MTH, who was having no medical or any surgical treatment to his upper limb, so primary spontaneous brachial artery pseudoaneurysm was diagnosed and patient was treated surgically without any complications. ABBREVIATIONS: PSA(pseudoaneurysm) MTH (Madina Teaching Hospital)